ANALISIS KEBIJAKAN PEMBANGUNAN KOTA TERPADU MANDIRI (KTM) UNTUK SEKTOR PERTANIAN DI KABUPATEN BANYUASIN, SUMATERA SELATAN - Indah Hermiati (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This research is related to the development policy of the Independent Integrated City (KTM) for the agricultural sector in the Regency. Banyuasin, South Sumatra. Telang KTM in Banyuasin Regency, South Sumatra regarding leakage of the region can occur at the Telang KTM in Banyuasin District, South Sumatra. The research method uses descriptive qualitative which is intended to describe people's behavior, field activities, and certain trapped and deep activities. The Telang KTM in Banyuasin Regency is not in accordance with the objectives of the policy and does not set goals in the development of the Telang KTM because the location of the trade center such as the KTM Telang market center is quite difficult to reach by rural communities. Difficulties in marketing agricultural products or crops due to limited access. Telang KTM which is quite difficult to reach by rural communities. Leakage occurred in areas (leakage) where the marketing of agricultural products directly outside the area Demand for Telang KTM products was still limited. As a result of the loss of territory because of the many farmers who sell agricultural goods out of the regions and cities.